Assessing energy transition costs: Sub-national challenges in Canada. (May 2022) - Stringer, Thomas; Joanis, Marcelin
Abstract: Transitioning from non-renewable sources of energy to renewable ones is an important theme in any national government's energy policy nowadays. However, the investments required for such a transition are often said to be quite costly. In Canada, previous research has shown that a transition is economically feasible at the national level, but is an energy transition equally as feasible for each of Canada's provinces? This paper uses energy use simulation data and a costing model to assess the infrastructure expenditures for a carbon-neutral transition for each of the country's ten provinces from now until 2060. By calculating the costs for five different scenarios and taking into account the savings incurred by lower fossil fuel consumption post-transition, we find that most of Canada's provinces stands to gain from a pan-Canadian energy transition by each capturing fossil fuel savings. We also find that generally, provinces that produce electricity using fossil fuels are set to benefit from more savings following a transition than provinces that currently produce electricity using renewable sources. Highlights: A cost-based model is introduced for decarbonizing Canada's energy system. The infrastructure costs and fossil fuel savings for each province are estimated. Most provinces stand to gain from an energy transition. Provinces that use fossil fuels for electricity production have the most to gain. Funding for clean energy projects should be promoted.